The Artificial Cascade of Cyrillo Volkmar Machado in the Lords of Belas`Farm: Challenges to its preservation - Braga, Sofia (2019)
This article intends to analyse the diverse artistic languages that are embodied in the artificial cascade-grotto and false ruin, conceived in 1798 by Cyrillo Volkmar Machado, in the garden of the Quinta de Belas, as well as its preservation challenges. Besides the transcultural languages patented in the idyllic garden of the Count and Countess of Pombeiro – the grotto and false ruin, perhaps the first one built in a Portuguese garden –, we will address the causes that led to the collapse of this artist’s unique project, as well as measures that may be taken to avoid its loss. Thus, we have the intention to raise awareness in the current owners and official entities of the importance of this structure in the pre-Romantic movement in Portugal.